Effect of Some Heavy Metal Ion on the Efficiency of Some Natural Dyes Solar Cells with Titanium Dioxide - Matter , Hamdy AB.; Ayad , Tariq M. (Scientific Journal of University of Benghazi, 2022)
Solar cells were made from natural pigments such as the anthocyanin pigment extracted from berry juice, henna leaves and roselle, betalain dye extracted from beets and red cabbage, and yellow curcumin dye extracted from turmeric with titanium dioxide. The ions of some metals are used with some dyes in the formation of cell electrodes with titanium oxide and zinc oxide. The mixture is heated to 450 ºC and makes electrodes that have a higher ability to absorb natural dyes, which increased the cell current and raised the percentage of cell efficiency. Natural red dyes (anthocyanins dye with the metals Cd, Zn, Pb, Hg, and Cu, dye-sensitized DSSCs have cell efficiency of 1.340%, 1.326%, 1,147%, 1,369%, and 1,325%, respectively. Betalain dyes, with the metals Zn, Hg, and Cu, dye-sensitized DSSCs have the cell efficiency of 1.369%, 1.385%, and 1.261%, respectively,) and natural yellow(curcumin dye) with the metals Zn, and Pb, dye-sensitized DSSCs have the cell efficiency of 1.301%, and 1.384%, respectively. This worked to increase the electrical conductivity of the electrodes. Possibly these inorganic substances act as aggregation factors for these pigments on the poles of the cell, which increases the efficiency of the cell.